Motion artefact reduction for reflection-mode photoplethysmography - Butler, Matthew J. (2018)
Photoplethysmography (PPG) is a technique that uses light to measure the local changes in blood-volume in subjects (predominantly humans). Multiple useful statistics can be gained from such a measurement; heart-rate and it's variability, blood-oxygen saturation and even an estimation of blood pressure, to name but a few. Compared to other measurement techniques, photoplethysmography is favourable as it is both non-invasive, since nothing physical penetrates the subjects skin, and safe, as the subject is galvanically isolated from the test equipment (additional benefits also exist).